CREATION OF ALGORITHM AND SOFTWARE TOOL FOR ASSESSMENT OF PROGRAMMING COMPLEXITY - Pirimqulova Zilola Avaz qizi (Scholar Express Journal, 2024)
In this article, "Creation of Algorithm and Software for Estimating the Complexity of Programming", the article discusses the complexities in the field of programming and the algorithms and software tools that evaluate them. The article covers topics such as news in the field of software technologies, explanation of the complexity of programming, features of algorithms and software tools. It is hoped that the article will help the readers to learn the intricacies of programming.
Keywords: algorithm and software tools; Testing and Completion; updating